(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The research focused on the advantages of using biodegradable waste in the canteen as an agricultural fertilizer in Grade 12 Accountancy, Business, and Management (ABM) Strandstudents at Bestlink College of the Philippines. Biodegradable waste inspires people’s creativity to use things that are already useless. It can also help students to be innovative. The researchers used the qualitative method. The research included 50 selected grade 12 ABM Strandstudents. Three variables were regarding the advantages of using biodegradable waste as agricultural fertilizer; these variables included saving money, helping the environment, and resourcefulness. The resourcefulness of the students is a factor of the advantages of using biodegradable waste as agricultural waste. In this aspect, students will also be creative and save their money by not buying fertilizers. The study also showed that improper waste disposal in the school canteen can affect the ambiance of the school. This result also showed that every person should be responsible for the school environment. This study showed the alternative things that every individual can make to reduce costs.